The Trend of Self-Regulated Learning Research on Physics Education - Pradana, Pramudya Wahyu (PILLAR OF PHYSICS EDUCATION, 2025)
Self-regulated learning has the potential to help optimize the effectiveness of physics learning. Therefore, research on self-regulated learning in physics education is vital. However, only limited studies exist on research trends related to this topic. For this reason, we are interested in capturing the characteristics of research about self-regulated learning in physics learning. This study was conducted to find out the characteristics of self-regulated learning in physics lessons and its future research directions.  The literature review method was used to address the research objectives. The article search used the keywords ‘Self-regulated learning’ OR ‘Self-directed learning’ AND ‘Physics’, with the article's publication date limited to between 2012 and 2024. This study reviewed 12 articles from the Scopus database. This review found that self-regulated learning research in physics context is still very limited regarding methods, research variables/objects, and learning topics. Physics topics that have been researched include heat, dynamic fluids, and atomic physics.This result indicates that there are still wide opportunities for studies on self-regulated learning in physics with variations in methods, research variables/objects, and learning topics. This research is expected to contribute insights regarding the characteristics of self-regulated learning studies on self-directed learning in physics education context and its future research opportunities.